2008
DOI: 10.1002/kin.20347
|View full text |Cite
|
Sign up to set email alerts
|

Induction period in the low‐temperature thermal oxidation of saturated hydrocarbons: Example of polyethylene

Abstract: Thermal oxidation of hydrocarbon substrates at low-to-moderate temperature, typically T ≤ 150 • C, results from a radical chain process initiated by hydroperoxide decomposition and displays an induction period. A reliable model exists to simulate oxidation kinetics, but an incertitude remains on initial steps because they are out of reach of all available analytical methods. This work is aimed to have a kinetic approach of the problem, by comparing various mechanisms, i.e., (A) bimolecular decomposition of ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“…It is warranted to consider that initial PE contains only hydroperoxides in an initial concentration [POOH] 0 , the decomposition of [POOH] 0 yielding to the same quantity of radicals than the overall unstable species initially present. Since POOH groups accumulate during oxidation while other eventually unstable species are consumed, the POOH decomposition rapidly becomes the largely predominant initiation process and this in fact justifies the mechanistic scheme chosen [22]. It was assumed that [PEOOH] 0 is equal to 10 À4 mol l À1 which is consistent with our other papers dealing with PE oxidation modeling.…”
Section: A Comparison Between Model Output Data and Chemiluminescencesupporting
confidence: 62%
See 1 more Smart Citation
“…It is warranted to consider that initial PE contains only hydroperoxides in an initial concentration [POOH] 0 , the decomposition of [POOH] 0 yielding to the same quantity of radicals than the overall unstable species initially present. Since POOH groups accumulate during oxidation while other eventually unstable species are consumed, the POOH decomposition rapidly becomes the largely predominant initiation process and this in fact justifies the mechanistic scheme chosen [22]. It was assumed that [PEOOH] 0 is equal to 10 À4 mol l À1 which is consistent with our other papers dealing with PE oxidation modeling.…”
Section: A Comparison Between Model Output Data and Chemiluminescencesupporting
confidence: 62%
“…All the kinetic parameters for polyethylene (k u2 , k b22 , k 22 , k 322 , k 622 and associated activation energies have been determined previously [5] hence will be used without change. They are shown in Table 2.…”
mentioning
confidence: 99%
“…For instance, the elastomers used as cable insulation in nuclear power plants are submitted to irradiation during their lifetime. Several studies have been devoted to the understanding of the consequences of ageing by gamma radiation on the mechanical properties of unfilled elastomers such as Ethylene-Propylene Diene Monomer (EPDM) or Poly DiMethyl Siloxane (PDMS) [1,2,3,4,5,6]. Thus, a scheme of the chemical reactions involved in the degradation process of EPDM under gamma radiation has been established from a fine analysis of the degradation products [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a scheme of the chemical reactions involved in the degradation process of EPDM under gamma radiation has been established from a fine analysis of the degradation products [3,4]. From a microstructural point of view, these reactions can be, within more or less important simplification, related to scissions and/or crosslinkings of the polymer chains [5,6] However in most applications, elastomers are formulated with fillers, which are in many cases nanoscopic. For instance, incorporation of nanoscopic silica fillers in elastomers is well known to improve their mechanical properties [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the following initial condition can be used [36]: The oxygen consumption rate is given, in non-diffusion controlled conditions by:…”
mentioning
confidence: 99%